Analysis of the Accuracy of INA-CBG’s Coding for Medical Rehabilitation Outpatients to Facilitate BPJS Claims at Hospital X - Setiatin, Sali; Sari, Hesti Puspita; Elvira, Shinta (International Journal of Psychology and Health Science, 2025)
The accuracy of diagnosis and procedure coding in the INA-CBG’s system is a key factor in the smooth submission of BPJS claims at hospitals. This study aims to analyze the relationship between the accuracy of coding and the validity of BPJS claims in medical rehabilitation outpatients at Hospital X. The method used is mixed methods with a sequential explanatory approach. The quantitative stage analyzed 2,216 patient claim files for January 2025 using the Chi-square test. Next, in-depth interviews were conducted with those responsible for managing outpatient claims to explore the causes of coding inaccuracies. The results show that 96.2% of files were coded correctly, 3.8% were coded incorrectly, and all are pending claims. The Chi-square test shows a significant relationship between coding accuracy and claim eligibility (p = 0.000). Qualitative findings revealed major obstacles in the form of differences in interpretation of coding, limited training in coding, and suboptimal hospital information systems. Regular training, improved coordination between units, and development of an electronic recording system in line with medical rehabilitation service needs are recommended. This study is expected to contribute to improving the quality of medical documentation and the effectiveness of health care financing through the INA-CBG’s claims system.